Cervical cancer incidence after screening with HPV, cytology, and visual methods: 18‐Year follow‐up of the Guanacaste cohort. Issue 8 (7th February 2017) - Rodríguez, Ana Cecilia; Ávila, Carlos; Herrero, Rolando; Hildesheim, Allan; Sherman, Mark E.; Burk, Robert D.; Morales, Jorge; Alfaro, Mario; Guillén, Diego; Trejos, María Ethel; Vargas, Rosa María; Torres, Guillermo; et al.
Abstract : Testing negative for human papillomavirus (HPV) predicts long‐term reassurance against invasive cervical cancer (ICC). To provide realistic estimates of effectiveness for new screening programs, we studied ICC risk after a 7‐year repeated multimethod screening effort. In 1993–1994, 10, 049 women aged 18–97 years were enrolled into a population‐based cohort study of cervical HPV in Guanacaste, Costa Rica. Women were screened at different intervals according to enrollment results. Each visit (mean 3.2, 90% attendance) included split‐sample conventional, automated, and liquid‐based cytology, visual inspection, cervicography, and PCR‐based HPV testing. Abnormal screening led to colposcopy and excisional treatment as appropriate during the study. Referral to colposcopy for HPV in the absence of other findings was introduced only at the last visit. Population‐based Costa Rica Cancer Registry linkage identified cohort women diagnosed with ICC in the 18 years following cohort enrollment. The ICC cumulative risk was 0.4% ( n = 38); 18 were diagnosed with ICC after study participation. Of these, 9 were missed at the screening step (negative screening or below the referral threshold, refused screening or colposcopy), 5 attended colposcopy but were not diagnosed as CIN2+, and 4 were treated for CIN2/3 but progressed to ICC nonetheless. Decreasing age‐standardized ICC rates for the 1993–2011 period were observed in Guanacaste; cohort women showed additional 31% ICC incidence reduction with apparent downstaging of cancers that occurred. ICC risk following negative HPV testing in the optimal age range 30–50 years was extremely low. Real‐life screening effectiveness following introduction is lower than the potential near‐complete efficacy predicted by HPV natural history. Abstract : What's new? Vaccines against human papillomavirus (HPV) help prevent infection with carcinogenic HPV types. HPV vaccination programs, however, generally target preadolescent girls, leaving older individuals dependent on secondary prevention via cervical cancer screening. This study, based on 18 years of follow‐up in the Guanacaste Natural History Study Cohort, highlights the importance of secondary prevention efforts in high‐risk regions. More than 10, 000 women in Guanacaste, Costa Rica, underwent repeated cervical screening with three kinds of cytology, visual methods, PCR‐based HPV testing, close follow‐up, and excisional treatment. Screening was associated with substantial but incomplete reduction in cervical cancer risk with likely downstaging of cancers.